NICKY UPSTAIRS AND DOWN - Ziefert, HARRIET, Harriet; Nakata, Hiroe (Penguin Young Readers New York, 2012)
Children plant pumpkin seeds, water and weed the garden patch, watch the pumpkins grow, pick them, and enjoy them in various ways